On Some Properties of Multiplicative Topological Indices in Silicon-Carbon - Abid Mahboob; Sajid Mahboob; Mohammed M. M. Jaradat; Nigait Nigar; Imran Siddique (Journal of Mathematics)
The use of graph theory can be visualized in nanochemistry, computer networks, Google maps, and molecular graph which are common areas to elaborate application of this subject. In nanochemistry, a numeric number (topological index) is used to estimate the biological, physical, and structural properties of chemical compounds that are associated with the chemical graph. In this paper, we compute the first and second multiplicative Zagreb indices (M1G and (M1G)), generalized multiplicative geometric arithmetic index (GAαIIG), and multiplicative sum connectivity and multiplicative product connectivity indices (SCIIG and PCIIG) of SiC4−Im,n and SiC4−IIm,n.